Aplikasi Pengolahan Data Penjualan Pembangkit Listrik Tenaga Surya Menggunakan Model View Controler Berbasis Framework Codelgniter Dan White Box Testing - Rafli, R; Fauziah, F; Aldisa, Rima Tamara (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Solar power plants are engaged in providing services and selling solar cells. The design of the sales data processing application uses a database and generates archiving data reports on the sales data report maker. To meet the needs of inputting sales data, there is a special section that handles the admin section, the cashier section, but this work system already uses a web-based data processing application. The method used in data processing applications is in the form of observation, interviews, and documentation. While the application design method uses document flow charts, data flow diagrams, and use cases. Supporting software in making data processing applications using the php database programming language used mysql. The design of the product sales data application produces a database design, namely the goods data and sales table. Black box test results show the features in the application run accordingly and the white box test results in the login menu generate the same region and path value of 7 for the value of Cyclomatic Complexity=7 , Region=7 and Independent Path=7, meaning that the logic used in the program code is appropriate and running and in accordance with the research objectives that the input process of stock goods and transactions can be done optimally.